Prevalence, trend and determining factors of gestational diabetes in Germany - Bock, Christina; Loerbroks, Adrian; Hornemann, Amadeus; Röhrig, Silke; Schneider, Sven (Geburtshilfe und Frauenheilkunde, 2012)
Purpose: The true prevalence of gestational diabetes in Germany is unknown. Thus, the studyʼs purposes were to estimate the prevalence of gestational diabetes as well as to describe the temporal prevalence trend and to identify determinants. Material and Methods: We calculated prevalence estimates based on two datasets: the register-based German perinatal statistic (n = 650 232) and the maternal self-reports from the German children and youth health survey (KiGGS; n = 15 429). Differences between prevalence estimates were analysed using χ2 and trend tests, and determinants were identified using logistic regression. Results: According to the perinatal statistic, gestational diabetes was present in 3.7 % of pregnant women in Germany in 2010. The prevalence across the years 2001 to 2006 was estimated at 1.9 % which differed significantly from the prevalence estimate derived from the KiGGS dataset for the same period of time (5.3 %; 95 % confidence interval: 4.6-6.1 %). Both datasets show an increasing trend of gestational diabetes (p < 0.001). The risk for gestational diabetes was mainly associated with age, BMI and social class of pregnant women as well as with multiple pregnancies. Conclusion: The lack of significant screening studies among representative samples hampers a sound estimation of the true prevalence of gestational diabetes in Germany. The increasing trend in gestational diabetes might continue due to the projected increase of important risk factors (e.g., maternal age, obesity). Our analyses support the current consensus recommendations regarding standardised gestational diabetes screening.